2010
DOI: 10.1007/s00248-010-9780-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics, Diversity and Function of Endophytic Siderophore-Producing Bacteria in Rice

Abstract: Siderophore production confers to bacteria competitive advantages to colonize plant tissues and to exclude other microorganisms from the same ecological niche. This work shows that the community of endophytic siderophore-producing bacteria (SPB) associated to Oryza sativa cultivated in Uruguayan soils is dynamic and diverse. These bacteria were present in grains, roots, and leaves, and their density fluctuated between log(10) 3.44 and log(10) 5.52 cfu g(-1) fresh weight (fw) during the plant growth. Less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(104 citation statements)
references
References 44 publications
1
100
0
3
Order By: Relevance
“…The compositions of bacteria related with iron cycling underwent great changes in different ARs and different stages. In the AR with UV/Cl 2 , at stage I, the relative abundance of nitrate-reducing bacteria (NRB) was 9.9%, and among them, 3.9% NRB were related to redox cycling of iron, such as Hyphomicrobium (3.7%) (Stein et al, 2001), and 6% NRB produced siderophores, including Sphingomonas (Duckworth et al, 2009), Brucella (Roop, 2012), Acinetobacter (Proschak et al, 2013) and Azospirillum (Loaces et al, 2011). The ironrespiring bacteria were 11.7%, predominantly including ironreducing bacteria (IRB) Acidobacterium (10.2%) (Nancucheo and Johnson, 2010) and iron-oxidizing bacteria (IOB) Pedomicrobium (1.3%) (Braun et al, 2009).…”
Section: 5mentioning
confidence: 99%
“…The compositions of bacteria related with iron cycling underwent great changes in different ARs and different stages. In the AR with UV/Cl 2 , at stage I, the relative abundance of nitrate-reducing bacteria (NRB) was 9.9%, and among them, 3.9% NRB were related to redox cycling of iron, such as Hyphomicrobium (3.7%) (Stein et al, 2001), and 6% NRB produced siderophores, including Sphingomonas (Duckworth et al, 2009), Brucella (Roop, 2012), Acinetobacter (Proschak et al, 2013) and Azospirillum (Loaces et al, 2011). The ironrespiring bacteria were 11.7%, predominantly including ironreducing bacteria (IRB) Acidobacterium (10.2%) (Nancucheo and Johnson, 2010) and iron-oxidizing bacteria (IOB) Pedomicrobium (1.3%) (Braun et al, 2009).…”
Section: 5mentioning
confidence: 99%
“…Soil microbes also secrete compounds having metal binding ligands such as siderophores, which enhance plant uptake of TEs [71,72]. Plant growth promoting bacteria also promote both mobilization of TEs from paddy soils and root growth by hormonal activities [73][74][75].…”
Section: Biological Processesmentioning
confidence: 99%
“…They reported that approximately 10% of the heterotrophic bacteria were able to produce siderophores in roots and leaves of young plants, but most of the heterotrophic bacteria were actively produced siderophore in mature plants. Siderophore production provides competitive advantages to endophytic bacteria for colonization of plant tissues and hence, excludes other microorganism from the colonization for the same ecological niche (Loaces et al, 2011). Siderophore production in nodule forming bacteria was investigated by Verma et al, (2012), they inoculate the nodule forming bacteria in the YEM media and conducted Chrome AzurolSulfonate (CAS) assay for formation of orange halos in blue agar plate.…”
Section: Siderophores Productionmentioning
confidence: 99%
“…It is one of the mechanisms used to compete with the plant pathogens. Loaces et al, (2011) studied the communities of siderophore producing endophytic bacteria from the grains, roots, and leaves of Oryza sativa cultivated on Uruguayan soils. They reported that approximately 10% of the heterotrophic bacteria were able to produce siderophores in roots and leaves of young plants, but most of the heterotrophic bacteria were actively produced siderophore in mature plants.…”
Section: Siderophores Productionmentioning
confidence: 99%